The Effectiveness of Team Teaching and Blended Learning Strategies in Speaking Class to Students with Different Personalities - Mazizah, Chilyatul; Suwandi, Suwandi; Hartono, Rudi (English Education Journal, 2021)
The aim of this research is to investigate how effective was the Team-teaching strategy and Blended learning to teach speaking to students with different personality types. This paper showed the result of experimental research on speaking skills to the introvert and extrovert students at Airlines Business Career Semarang. A 2x2 factorial design of experimental research was used to collect the data from 52 students which was divided into two groups; they were experimental group 1 and experimental group 2. They were treated with different strategies: Team-teaching and Blended learning strategies. In the Team-teaching class, there are two teachers taught in one class. Meanwhile, in Blended learning class, the teacher blended the face-to-face meeting and also the online meeting. The instrument of this research was observation checklist, questionnaire, pre-test, and post-test. The data was analyzed using ANOVA to prove the hypotheses. The result showed that Team-teaching was more effective to teach speaking to the students with introvert and extrovert personality. Based on the analysis of ANOVA there were no interaction among team teaching and blended learning strategies, students’ personality, and speaking skill